2022
DOI: 10.1016/j.jinf.2021.12.037
|View full text |Cite
|
Sign up to set email alerts
|

Implementation study of SARS-CoV-2 antigen lateral flow tests in men's professional (Premiership) rugby union sports squads in England during the COVID-19 pandemic

Abstract: This study evaluated the validity and utility of antigen-detection rapid diagnostic tests (Ag-RDTs) for SARS-CoV-2 in elite sports. The data on utility, ease of use and application for Ag-RDTs as a new testing format were positive from players and staff. This evaluation was limited by the low prevalence of SARS-CoV-2 circulating within the three squads. This study highlights the need for continued service evaluations for SARS-CoV-2 Ag-RDTs in elite sport settings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The uptake of Ag-RDTs was higher among individuals with COVID-19 symptoms, healthcare workers, refugees, individuals who had received two or more doses of vaccine, and individuals identified at TB clinics than it was among other groups. Previous studies have shown good overall uptake of Ag-RDTs among different populations, especially among symptomatic individuals [ 18 , 19 ]. The reasons for the lower uptake of Ag-RDTs among those aged less than 18 years and among individuals in Afrin and Idleb districts could not be determined from the interviews with CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…The uptake of Ag-RDTs was higher among individuals with COVID-19 symptoms, healthcare workers, refugees, individuals who had received two or more doses of vaccine, and individuals identified at TB clinics than it was among other groups. Previous studies have shown good overall uptake of Ag-RDTs among different populations, especially among symptomatic individuals [ 18 , 19 ]. The reasons for the lower uptake of Ag-RDTs among those aged less than 18 years and among individuals in Afrin and Idleb districts could not be determined from the interviews with CHWs.…”
Section: Discussionmentioning
confidence: 99%
“…If PCR testing is not feasible, we recommend regular rapid antigen testing on a daily base, but at least twice a week. Rapid antigen test is easy to perform and has shown high acceptance in athletes (Finch et al, 2022 ). Recommending a more frequent testing strategy goes in line with the findings of Kamo et al, who investigated the effectiveness of different COVID-19 testing strategies.…”
Section: Discussionmentioning
confidence: 99%
“… In asymptomatic patients ≥12 years old without risk factors for severe COVID-19, we suggest the use of laboratory-based NAAT versus rapid antigen testing for the diagnosis of COVID-19. Weak against Low [ 11 , 20 , 49 , 54 , 55 , 65 , 70 , 71 , 77 , 83 , 89 , 94 , 22 , 111 , 113 , 121 , 128 , 130 , 137 , [143] , [144] , [145] , [146] , 24 , [147] , [148] , [149] , 158 , [160] , [161] , [162] , [163] , [164] , [165] , 28 , [166] , [167] , [168] , [169] , [170] , [171] , [172] , [173] , [174] , [175] , 34 , 176 , 40 , 43 , 44 , 46 ] 3 In asymptomatic people of any age with any risk factor(s) for severe COVID-19 (including age <3 or ≥65 years) should rapid antigen tests be used, as compared to laboratory-based ...…”
Section: Questions Addressed By the Guideline Updatementioning
confidence: 99%
“… In asymptomatic people, we suggest the use of laboratory-based NAAT in non-nasopharyngeal/non-saliva respiratory samples versus rapid antigen testing in non-nasopharyngeal/non-saliva for the diagnosis of COVID-19. Weak against Low [ 107 , 110 , 128 , 154 , 156 , 159 , 164 , 167 , 171 , 111 , 112 , 118 , [120] , [121] , [122] , 124 , 126 ] 6 In asymptomatic people should rapid antigen tests be used in saliva samples as compared laboratory based NAAT to diagnose COVID-19? In asymptomatic people, we suggest the use of laboratory-based NAAT in saliva samples versus rapid antigen testing in saliva for the diagnosis of COVID-19.…”
Section: Questions Addressed By the Guideline Updatementioning
confidence: 99%